2021
DOI: 10.1029/2020gl092087
|View full text |Cite
|
Sign up to set email alerts
|

Northeast Siberian Permafrost Ice‐Wedge Stable Isotopes Depict Pronounced Last Glacial Maximum Winter Cooling

Abstract: Stable isotopes (δ18O, δD) of wedge ice hold potential to reconstruct past winter climate conditions. Here, we present records of the marine isotope stages (MIS) 3 and 2 including the last Glacial maximum (LGM) from Bol’shoy Lyakhovsky Island (NE Siberia). MIS 3 wedge ice dated from 52 to 40 Kyr b2k varies between −32 and −29‰ in δ18O. Colder LGM conditions are implied by δ18O of −37‰ around 25 Kyr b2k. Similar Deuterium excess values indicate comparable moisture sources during MIS 3 and MIS 2. Regional LGM cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Other aquatic fossils such as from branchiopods, cladocerans and chironomids have only little been studied yet in Yedoma IC deposits (Neretina et al, 2020;Rogers et al, 2021). Numerical reconstructions of paleo-climate parameters such as summer air temperature and annual precipitation in West Beringia are scarce (Andreev et al, 2011) or poorly developed in case of ice-wedge stable water isotopic composition reflecting winter climate (Opel et al, 2018;Wetterich et al, 2021). Pitulko et al (2017) present T July and precipitation reconstructions from 34 to 10 kyr BP for the western part of the Yana-Indigirka Lowland (east of our study region), while from the Bykovsky Yedoma archive only two points in time, at around 48 and 35 kyr BP, provide estimated T July values based on plant macrofossils (Kienast et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other aquatic fossils such as from branchiopods, cladocerans and chironomids have only little been studied yet in Yedoma IC deposits (Neretina et al, 2020;Rogers et al, 2021). Numerical reconstructions of paleo-climate parameters such as summer air temperature and annual precipitation in West Beringia are scarce (Andreev et al, 2011) or poorly developed in case of ice-wedge stable water isotopic composition reflecting winter climate (Opel et al, 2018;Wetterich et al, 2021). Pitulko et al (2017) present T July and precipitation reconstructions from 34 to 10 kyr BP for the western part of the Yana-Indigirka Lowland (east of our study region), while from the Bykovsky Yedoma archive only two points in time, at around 48 and 35 kyr BP, provide estimated T July values based on plant macrofossils (Kienast et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, radiocarbon dating of the carbon dioxide in air bubbles and the organic carbon dissolved within the wedge ice showed much younger age than host sediments, and some Pleistocene ice wedges in the old Tunnel formed between 28,000 and 22,000 years BP while the age of host sediments exceeded 35,000 years BP (Lachniet et al, 2012). Similar studies in other regions (Opel et al, 2019;Holland et al, 2020;Wetterich et al, 2021) also found that ice wedges may be several thousand years younger than enclosing sediments. We hope a similar approach will be used during the future studies in the new Tunnel.…”
Section: Age and Nature Of Ice Wedges In Yedomamentioning
confidence: 64%
“…The stratigraphic classification of the middle Pleistocene to the Holocene in the East Siberian Arctic lowlands is based mostly on palynological (e.g., Gitermann et al, 1982;Kaplina and Lozhkin, 1984), palaeozoological (e.g., Sher, 1971;Vangenheim, 1977), and cryolithological (e.g., Kaplina, 1981;Kaplina, 1989;Tumskoy, 2012) and geochronological data (e.g., Schirrmeister et al, 2002a;Schirrmeister et al, 2003a;Schirrmeister et al, 2008;Schirrmeister et al, 2011b;Andreev et al, 2004;Andreev et al, 2009;Wetterich et al, 2009;Wetterich et al, 2011;Wetterich et al, 2014;Wetterich et al, 2016;Wetterich et al, 2019;Wetterich et al, 2020;Wetterich et al, 2021;Zimmermann et al, 2017). The study of local profiles resulted in numerous separate stratigraphic schemes, often with individual terms for single suites, layers, or horizons, which were correlated for further chronostratigraphic classification.…”
Section: Study Regionmentioning
confidence: 99%
“…In total, 486 samples were studied for heavy mineral associations of the fine fraction (63-125 µm) and in 282 of these samples the coarse fraction (125-250 µm) was additionally analyzed. Lisiecki and Raymo, 2005) used in this work according to Andreev et al (2004Andreev et al ( , 2009, Wetterich et al (2019Wetterich et al ( , 2021 and Zimmermann et al (2017) Furthermore, light mineral associations were studied in 242 samples of the fine fraction and 131 samples of the coarse fraction (Table 2).…”
Section: Analytical Studiesmentioning
confidence: 99%